Challenges of New Colombian Coffee Brand Market Entry in Switzerland with a Focus on the Zurich Market - Parokkaran Mohan, Amal (Digital Repository of Theses - SSBM Geneva, 2025)
The current study titled CHALLENGES OF NEW COLOMBIAN COFFEE BRAND MARKET ENTRY IN SWITZERLAND WITH A FOCUS IN THE ZURICH MARKET aimed to explore the various challenges that are currently existent in bring Colombian coffee into the Swiss market, with a focus on the Zurich market. The research employed a qualitative research design with four main objectives of mapping and analysing the competitive landscape of major coffee chains and brands operating in Zurich, identifying consumer segments within the Zurich coffee market differentiated by behaviours, preferences, and price sensitivity, and to recommend a go- to-market strategy leveraging local partnerships, community events, and marketing channels reflective of Swiss consumer priorities. The research used a semi-structured interview to explore experiences of Colombian coffee producers who are trying to bring their brand into the Zurich market, and with industry experts in the Swiss coffee market. Thematic analysis was used to analyse the interview responses and findings were divided based on the two sections of sample interviewed. Important challenges were identified for both the sets of the sample. Analysis of interviews for the coffee producers yielded the themes of market entry challenges, sustainable and ethical sourcing and branding and marketing approaches. Each of the themes had their sub- themes highlighting specific challenges that Colombian coffee producers face in finding a foothold within the Swiss market. The thematic analysis of interviews from industry experts also yielded three important themes which included Brand loyalty as challenge for new entrants, Pricing dynamics and Change, trend and innovation. Both these sets of findings show that the Swiss coffee market is highly saturated and entrenched with already existing brands with longstanding loyalty with their customers. Colombian coffee producers will have to therefore identify and develop effective and relevant marketing strategies to be able to establish themselves within the highly competitive market. There is a general lack of awareness about the Colombian coffee heritage which needs to be changed in order for Colombian brands to survive in a Zurich market. Therefore, findings from this research can be utilised as a basis for producers and importers to identify challenges and find effective strategies that will differentiate the Colombian coffee brands from already existing brands in the Zurich markets. Key Words: Colombian coffee, coffee producers, industry experts, brand differentiation, challenges in market entry, Zurich coffee market